Research on the aging characteristics of base liquor in Sichuan Province’s strong Aroma Baijiu at different aging periods using mass spectrometry and 3D fluorescence spectroscopy methods - Qing He; Guoquan Han; Hongfei Yao; Jun Wang; Dongxian Geng; Qiuyue Han; Xiao Wang; Kechun Tang (PLoS ONE, 2026)
The aging process of Baijiu directly impacts its flavor and quality, yet the chemical changes during aging lack systematic analysis. This study focused on Luzhou-flavor base liquor from Sichuan Province, aiming to elucidate the compositional evolution across different aging periods and provide a scientific foundation for Baijiu quality enhancement. Volatile flavor compounds were detected using gas chromatography–mass spectrometry (GC-MS), and metabolomic analysis was employed to screen multiple potential biomarkers. Combined with OPLS-DA, their variation characteristics across different aging periods were further investigated. In addition, three-dimensional fluorescence spectroscopy was employed to investigate the correlation between flavor components and aging duration, while odor activity values (OAVs) were calculated to evaluate the contribution of key compounds to the overall flavor profile. Results showed that 75 flavor compounds were detected across five aging periods (1, 5, 10, 15, and 20 years). As aging progressed, the concentration of esters decreased significantly from 95.56 mg/L at year 5 to 24.04 mg/L at year 20. Acid content peaked at 97.29 mg/L in the fifth year and gradually declined thereafter. Alcohols and polyphenols reached their maximum concentrations at year 10 (87.96 mg/L) and year 15 (80.67 mg/L), respectively, followed by a marked decline. These trends reveal the dynamic evolution of different flavor substances throughout the aging process. Among these changes, a “redshift” phenomenon in fluorescence spectra was observed, reflecting increased molecular complexity and a notable enhancement in flavor richness. These findings highlight the critical impact of the chemical evolution of base liquor components on aroma and quality. The results provide theoretical support for understanding the aging mechanism of Baijiu and optimizing its processing techniques, laying a scientific foundation for quality control and market promotion efforts.